The Phantom Eye: New Zealand and the Five Eyes - Battersby J; Ball R (Taylor and Francis Group, 2023)
New Zealand’s involvement in the Five Eyes is under-reported in academic and general literature. New Zealand’s participation was initially due to its integration within World War II western alliance intelligence systems, which evolved further after the war ended. Once in, New Zealand’s role became something of a self-fulfilling prophecy, but genuine nonetheless. Changes in communications technology, access to US technical capability, and geopolitical changes in the Pacific have all led to a viable New Zealand role in Five Eyes, as both contributor and beneficiary. But to retain this, New Zealand must increase its foreign intelligence capability in the future.